EU Peacebuilding Missions Developing Security in Post-conflict Nations - Doyle, Kieran (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book explores the EU's approach to peacebuilding and questions the EU global role as crisis manager and capacity builder. It highlights the significant contributions of the EU to civilian peacebuilding and also critically evaluates the activities of the EU Common Security and Defence Policy (CSDP) within their rule of law and human rights peacebuilding missions. It draws on the author's twenty years of experience working on CSDP and EU defence matters including his research on EU police missions in Africa and Middle East. It exposes emergent tension between peacebuilding in its neighbourhood and security issues. It examines the practice of EU peacebuilding including performance of its missions and how deployed personnel can professionalise their diplomatic (mediation, negotiation and dialogue facilitation) capacity to fully realise the potential of missions and exploit opportunities for expanding the vision of peace. It formulates convincing policy recommendations for the future planning of EU external relations in post conflict environments and offers valuable insights into how to connect with people and communities in the aftermath of conflict. Kieran Doyle is Lecturer in the Department of International Development and Assistant Director of the Edward M Kennedy Institute for Conflict Intervention, Maynooth University, Republic of Ireland. He is Irish representative on the Academic Board of the European Security and Defence College (ESDC) based in the European External Action Service, Brussels, and has represented Ireland on the Academic Think Tank of the Organisation of Security and Cooperation in Europe (OSCE).
1. CSDP and alignment with supranational goals of the Union -- 2. Where the EU has fitted in on the ground (integrated approach) -- 3. Getting under the Skin -- 4. Transformational Leadership, Soft Power, Building Trust and understanding the root causes of conflict for a sustaining peace -- 5. Conclusion - Connecting the Head with the Heart and Feet. .
Keywords: Criminology; Human rights; Peace; Security, International; Politics and war; International criminal law; Crime Control and Security; Human Rights; Peace and Conflict Studies; International Security Studies; Military and Defence Studies; International Criminal Law